Pengembangan Media Wayang Karakter Binatang (Wakarbin) pada Materi Bercerita di Kelas II SDN 32 Palembang - Adelina Siregar; Bambang Hermansah; Imelda Ratih Ayu (Journal on Education, 2024)
The animal character puppet media (wakarbin) developed in this study is made of plywood which is painted using watercolors that are adjusted to the color of the animal characters in the story, then given a handle so they can stand up and equipped with a story box with a background that matches the setting in the story. The research method used is R&D (Research and Development). The procedure used is the ADDIE model which consists of five stages, namely 1) Analyze, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The results of validating the development of animal character puppet media (wakarbin) on storytelling material have a high level of validity. Based on the results of criticism and suggestions as well as assessments from the validators, the responses of grade II elementary school students and teachers of SD Negeri 32 Palembang were "very valid" and "very practical". Assessments from media experts who were validated by the validator obtained a percentage of 93.33% with a very valid category. Assessment of material experts validated by the validator obtained a percentage of 86.66%, with the category "very valid". Assessment of teacher responses obtained a percentage of 90.66% with a very valid category. The practicality assessment obtained from student responses was 94.66%, in the "very practical" category.